2015
DOI: 10.1016/j.bmc.2015.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological profiling and mechanistic studies of 4-aminoquinoline-based heterodimeric compounds with dual trypanocidal–antiplasmodial activity

Abstract: Dual submicromolar trypanocidal-antiplasmodial compounds have been identified by screening and chemical synthesis of 4-aminoquinoline-based heterodimeric compounds of three different structural classes. Inhibition of the enzyme trypanothione reductase seems to be involved in the potent trypanocidal activity of these heterodimers but likely it is not their main biological target within Trypanosoma brucei. Regarding their antiplasmodial activity, the heterodimers seem to share the mode of action of the antimalar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…We recently found that both homodimerization and heterodimerization of the 4-aminoquinoline derivative huprine Y results in increased potency against T. brucei and improved selectivity over mammalian cells relative to the parent compound,36, 37 albeit at the expense of increasing lipophilicity and molecular weight. In this current paper, we have explored the effect on antitrypanosomal activity of the introduction of a side chain, featuring a terminal cyano, amino, or guanidino group, at the primary amino group of huprine Y or the simpler structurally related tacrine or 6-chlorotacrine, as an alternative approach to improve the antitrypanosomal profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that both homodimerization and heterodimerization of the 4-aminoquinoline derivative huprine Y results in increased potency against T. brucei and improved selectivity over mammalian cells relative to the parent compound,36, 37 albeit at the expense of increasing lipophilicity and molecular weight. In this current paper, we have explored the effect on antitrypanosomal activity of the introduction of a side chain, featuring a terminal cyano, amino, or guanidino group, at the primary amino group of huprine Y or the simpler structurally related tacrine or 6-chlorotacrine, as an alternative approach to improve the antitrypanosomal profile.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we have found that homodimerization of huprine Y (as in compound 2 , 36 Fig. 1) and heterodimerization with the 4-aminoquinoline derivative tacrine (as in compound 3 , 37 Fig. 1) also results in up to 3-fold increased potency and selectivity against T. brucei .…”
Section: Introductionmentioning
confidence: 97%
“…The majority of heteronuclear quinoline dimers 31 showed considerable activity against CQR K1 strain with IC 50 in nanomolar level, and half of them (IC 50 : 350‐470 nM) were more active than CQ (IC 50 : 930 nM) . Compared with the unsubstituted analogs, hybrids with ‐Cl at R position displayed lower activity.…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%
“…Since then, several TR inhibitors have been discovered by using the models of Zhang and Jacoby, especially the aminoacridine (7), a higher homolog of (6), as described by Bonse et al[ 51 ], and a pyridazine (8) and a carbazole (9) described by Horvath[ 52 ]. More recently, the inhibitory activity of more potent derivatives such as thioridazine (10) and aminoquinoline (11) was described by Lo Presti et al[ 53 ] and Sola et al[ 54 ], respectively.…”
Section: Trypanothione Reductasementioning
confidence: 99%